Shock Hugoniot Data for Water up to 5 Mbar Obtained with Quartz Standard at High-Energy Laser Facilities. (11th December 2021) - Mancelli, D.; Errea, I.; Tentori, A.; Turianska, O.; Larreur, H.; Katagiri, K.; Ozaki, N.; Kamimura, N.; Kamibayashi, D.; Ishida, K.; Ogura, H.; Kawasaki, K.; et al.
Abstract : In this work, we present experimental results on the behavior of liquid water at megabar pressure. The experiment was performed using the HIPER (High-Intensity Plasma Experimental Research) laser facility, a uniaxial irradiation chamber of GEKKO XII (GXII) at the Institute of Laser Engineering (ILE), and the PHELIX at GSI (GSI Helmholtz Centre for Heavy Ion Research), a single-beam high-power laser facility, to launch a planar shock into solid multilayered water samples. Equation-of-state data of water H 2 O are obtained in the pressure range 0.50–4.6 Mbar by tuning the laser-drive parameters. The Hugoniot parameters (pressure, density, etc.) and the shock temperature were simultaneously determined by using VISAR and SOP as diagnostic tools and quartz as the standard material for impedance mismatch experiments. Finally, our experimental results are compared with hydrodynamic simulations tested with different equations of state, showing good compatibility with tabulated SESAME tables for water.